Assessing the Threat of Amphibian Chytrid Fungus in the Albertine Rift: Past, Present and Future. - Tracie A Seimon; Samuel Ayebare; Robert Sekisambu; Emmanuel Muhindo; Guillain Mitamba; Eli Greenbaum; Michele Menegon; Fabio Pupin; Denise McAloose; Alyssa Ammazzalorso; Danny Meirte; Wilbur Lukwago; et al. (PLoS ONE, 2015)
Batrachochytrium dendrobatidis (Bd), the cause of chytridiomycosis, is a pathogenic fungus that is found worldwide and is a major contributor to amphibian declines and extinctions. We report results of a comprehensive effort to assess the distribution and threat of Bd in one of the Earth's most important biodiversity hotspots, the Albertine Rift in central Africa. In herpetological surveys conducted between 2010 and 2014, 1018 skin swabs from 17 amphibian genera in 39 sites across the Albertine Rift were tested for Bd by PCR. Overall, 19.5% of amphibians tested positive from all sites combined. Skin tissue samples from 163 amphibians were examined histologically; of these two had superficial epidermal intracorneal fungal colonization and lesions consistent with the disease chytridiomycosis. One amphibian was found dead during the surveys, and all others encountered appeared healthy. We found no evidence for Bd-induced mortality events, a finding consistent with other studies. To gain a historical perspective about Bd in the Albertine Rift, skin swabs from 232 museum-archived amphibians collected as voucher specimens from 1925-1994 were tested for Bd. Of these, one sample was positive; an Itombwe River frog (Phrynobatrachus asper) collected in 1950 in the Itombwe highlands. This finding represents the earliest record of Bd in the Democratic Republic of Congo. We modeled the distribution of Bd in the Albertine Rift using MaxEnt software, and trained our model for improved predictability. Our model predicts that Bd is currently widespread across the Albertine Rift, with moderate habitat suitability extending into the lowlands. Under climatic modeling scenarios our model predicts that optimal habitat suitability of Bd will decrease causing a major range contraction of the fungus by 2080. Our baseline data and modeling predictions are important for comparative studies, especially if significant changes in amphibian health status or climactic conditions are encountered in the future.